Economic and environmental benefits of recovery networks for WEEE in Europe. (10th June 2019) - Messmann, Lukas; Helbig, Christoph; Thorenz, Andrea; Tuma, Axel
Abstract: The EU directive on Waste Electrical and Electronic Equipment (WEEE) imposes the obligation to collect a large share of the end-of-life products on electronics manufacturers. Environmental aspects, however, are often considered only rudimentarily. Based on previous research and real-world data, a mixed-integer linear programming (MILP) model of a European reverse network for WEEE is developed, including collection, high-value recovery, or third-party collection and recycling. The results comprise optimal network decisions and corresponding opportunity costs for economic and 21 environmental categories (18 midpoints, 3 endpoints). The evaluation of the environmental impact is based on data from the ecoinvent database, characterized using the ReCiPe 2016 Life Cycle Impact Assessment (LCIA) method. The results unveil conflicts and congruencies between the objectives. Collection and high-value recovery are preferable in up to six countries for economically optimal networks and in up to 15 countries with optimal benefit for global warming and fossil resource depletion. Discrepancies in objective values are larger between economic and most of the environmental solutions than in between most of the environmental ones. The dimensions land use and freshwater eutrophication show the least conflicts with the economic rationale. Solutions for mineral resource depletion prefer third-party collection and recycling. Conflicts between solutions are resolved by the ε-constraint method. Sensitivity analyses show the robustness of key findings. This study emphasizes the importance of a broad assessment of environmental impacts as well as mutual economic and environmental opportunity costs in large-scale recovery networks for WEEE. Highlights: Generic MILP model for reverse network design for WEEE recovery applied to the EU. Environmental data for 3 endpoints and 18 midpoints from ecoinvent with ReCiPe 2016 Computational results for economic and 21 environmental objectives in 20 scenarios. Analysis of conflicts, congruencies, and Pareto-efficiencies between objectives.